2017
DOI: 10.1038/s41467-017-01718-7
|View full text |Cite
|
Sign up to set email alerts
|

Mapping tenascin-C interaction with toll-like receptor 4 reveals a new subset of endogenous inflammatory triggers

Abstract: Pattern recognition underpins innate immunity; the accurate identification of danger, including infection, injury, or tumor, is key to an appropriately targeted immune response. Pathogen detection is increasingly well defined mechanistically, but the discrimination of endogenous inflammatory triggers remains unclear. Tenascin-C, a matrix protein induced upon tissue damage and expressed by tumors, activates toll-like receptor 4 (TLR4)-mediated sterile inflammation. Here we map three sites within tenascin-C that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 62 publications
2
83
0
Order By: Relevance
“…This occurs via the binding of damage associated molecular patterns (DAMPs) including HMGB1, heat shock and S100 proteins 100,101 . Tenascin-C a matrix protein induced upon tissue damage also activates TLR4 mediated sterile inflammation 102 . Binding of these ligands to TLR4 induces a high alert state, favouring the development of chronic inflammation 50,103 .…”
Section: Cross Talk Between Cells Of Mesenchymal Originmentioning
confidence: 99%
“…This occurs via the binding of damage associated molecular patterns (DAMPs) including HMGB1, heat shock and S100 proteins 100,101 . Tenascin-C a matrix protein induced upon tissue damage also activates TLR4 mediated sterile inflammation 102 . Binding of these ligands to TLR4 induces a high alert state, favouring the development of chronic inflammation 50,103 .…”
Section: Cross Talk Between Cells Of Mesenchymal Originmentioning
confidence: 99%
“…Crystallisation of the FBG domain of human tenascin-C in complex with Fab fragments of C3 revealed interactions in the X-ray structure are mediated by hydrogen bonds and three layer pi:pi stacking, predominantly between one of the two Fab chains (figure 2A,B). Comparison of the TLR4 binding epitope10 with the Fab epitope in FBG predict that antibody binding will abrogate tenascin-C’s ability to activate TLR4 by preventing access of the receptor to residues (S2131 and I2133) in FBG that are required for optimal binding to TLR4. This was validated experimentally by demonstration that preincubation of FBG with C3 inhibits binding of FBG to purified recombinant TLR4 in a solid phase binding assay (IC 50 45.56 nM)(figure 2C) and that preincubation of FBG with C3 blocks the ability of FBG to induce cytokine synthesis in primary human macrophages, while C3 had no effect on LPS-induced cytokine release (figure 2D).…”
Section: Resultsmentioning
confidence: 99%
“…Mapping the active domain within tenascin-C revealed a unique structural epitope in the fibrinogen-like globe (FBG) that is essential for binding to and activating TLR4 8 10. Distinct modes of receptor activation and diverse downstream signalling induced by FBG compared with pathogenic TLR4 agonists,11 revealed an opportunity to ablate pathological ‘sterile’ inflammation, leaving intact host defence against infection.…”
Section: Introductionmentioning
confidence: 99%
“…Tenascins belong to the fibrinogen-related proteins (FREPs) family that all bear an FBG domain. If not all FBG domains are able to activate TLR4, Zuliani-Alvarez et al showed that the presence of a cationic ridge in the FBG domain defined the capacity to activate TLR4 46 .…”
Section: Discussionmentioning
confidence: 99%